Generation of wealth from waste management practices among rural dwellers in Afijio Local Government Area of Oyo state (2013)
The study investigated potentials of generating wealth from waste management practices among rural dwellers in Afijio local government area of Oyo state. A multi-stage sampling procedure was used to select 165 respondents. Identified waste types commonly generated by the respondents were food scraps (84%), plastic containers (62.3), nylon wraps (61.1%) and paper and cartons (60.5%). while waste management practices were burning (75.9%) and use of dunghills (55.6%). Some of the constraints faced by the respondents were lack of knowledge on the value of waste, lack of equipment for wealth generation activities, and time constraint. No significant relationship was observed between respondents sex (x2 = 0.419, p>0.811), marital status (x2= 9.34, p>0.053) and extent of wealth generation from waste management. However there was significant relationship between respondents' age (x2 = 15.95, p<0.043), educational qualification (x2 = 28.25, p<0.001) and extent of wealth generation from waste management. Also, no significant relationship was established between the types of waste generated by respondents and their extent of wealth generation from waste management (x2=-1.68, p>0.795). However, there was significant relationship between constraints faced by respondents in utilizing the wealth generation opportunities and their extent of wealth generation from waste management (r=-0.281, p<0.000). The study concluded that most of the respondents disposed of their waste instead of converting them to wealth thereby underutilizing wealth generation opportunities for most of the waste types.